Uzbekistan - Finland Pedagogical Institute (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The issues of teaching the lexicology level of the Uzbek language have been studied to some extent by Uzbek linguists and Methodist scholars. At the beginning of the 20th century, the school textbooks created by Abdurauf Fitrat, Shorasul Zunun, Munavvar Qori, Qayyum Ramazan, Elbeklar, and later Murad Shams, Tokhtanazar Shermuhamedov, Khalil Qayumov, Subutoy Dolimov, Qayyum Hakimov, took place, albeit briefly, in the textbooks.